Preserving Sunda Kelapa port as a heritage tourism with a sustainable tourism approach to increase tourist visiting interest - Lim, Elsye; Berutu, Feronika (Jurnal Pariwisata Pesona, 2025)
Sunda Kelapa Harbor is a historic site with high cultural value and great potential as a heritage tourism destination in Jakarta. However, tourist interest remains low due to insufficient promotion, inadequate facilities, and low awareness of cultural heritage preservation. This study aims to analyze efforts to preserve Sunda Kelapa Harbor as a heritage tourism site through a sustainable tourism approach in order to increase tourist interest. This study employs a descriptive qualitative method, utilizing observation, in-depth interviews, and documentation techniques. Data for this study was collected from March to April and conducted directly in the Sunda Kelapa Port area. The results of this study indicate that the preservation of the Sunda Kelapa Port area can be achieved through several strategies, such as improving supporting infrastructure, educating the community and tourists, and strengthening digital-based promotion to ensure the sustainability of this heritage area. With the right strategies, Sunda Kelapa Port has great potential to develop as a premier heritage tourism destination that can preserve historical value while also generating positive economic impacts for the surrounding community. Through this research, the researchers have identified the factors influencing the low tourist visitation rates and formulated strategic recommendations that can be implemented to enhance the area's appeal. These findings are expected to contribute meaningfully to the development of sustainable and attractive heritage tourism management for both domestic and international tourists.